(untitled) (Jurnal Bina Praja, 2025)
Waste management in Malang City involves diverse stakeholders with unequal power, legitimacy, and urgency, leading to coordination challenges and gaps in policy implementation. This study aims to analyze the configuration of waste management stakeholders using the Stakeholder Salience Framework to identify stakeholder classes, map interests, and explain the implications of attributing imbalances on governance failure. A qualitative approach was used to collect data through interviews, observations, and document reviews. Informants were purposively selected from government actors, technical units, the private sector, waste management startups, communities, and the public. Findings indicate that formal power is concentrated among government stakeholders, who are the dominant and definitive actors. At the same time, the urgency of waste management lies with community stakeholders, technical units, and field actors. This configuration demonstrates an imbalance that creates a structural disconnect between policy formulation and operational practices, leading to policies that are administrative, less responsive, and lack substantive collaboration. These findings confirm that governance failure is not solely due to weak coordination but rather to the unequal distribution of stakeholder attributes. Conceptually, this study extends the application of the stakeholder salience framework by showing that the level of salience is dynamic and can be engineered through institutional interventions that reorganize the distribution of power in urban waste governance.